Aloin promotes cell apoptosis by targeting HMGB1-TLR4-ERK axis in human melanoma cells - Li, Pan; Ren, Kai; Liang, Yin yin; Liu, Ji kai; Liang, Zhuo wen; Zhang, Yong feng (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
Aloin (ALO) is the major anthraquinone glycoside purified from the Aloe species. It is well known for its anti-tumor effects. However, the protective effects of ALO in melanoma cancer and underlying molecular mechanism remain unclear. High-mobility group protein B1 (HMGB1) is an intracellular protein, which has closely association with cell survival, proliferation and metastasis in various cancers. In this study, we explored the effect of ALO on cell survival and apoptosis by targeting HMGB1 signal pathway. We confirmed that ALO exerts a strong effect on promoting cell apoptosis of melanoma cells in vitro. Furthermore, HMGB1 release was significantly inhibited in melanoma cancer cells treated with ALO. Knockdown of HMGB1 could enhance melanoma cell death that is induced by ALO treatment. Moreover, HMGB1 facilitated ALO mediated melanoma cell apoptosis by binding to its receptor, Toll-like receptor 4 and activating extracellular regulated protein kinases (ERK) signal pathway. Altogether, our study demonstrated that ALO plays an important role in promoting apoptosis of melanoma cells by inhibiting HMGB1 release and activation of downstream ERK signal pathway.
EXCLI Journal;Vol. 19. 2020, p. 641-651
Keywords: Aloin; Melanoma; Apoptosis; HMGB1; ERK signal pathway; 610